Research on Customized Telecommunication Product Structural Modeling and Configuration Based on Modular Product Family - Wenya Chou (Dianxin kexue)
According to the plurality and individuation of the customers'demands, a customized telecommunication product configuration model was established on the basis of the modular product family structure GBOM. The configuration modules were categorized as basic configuration modular, essential modular and optional modular complying with the configurability of telecommunication products. Five-element information expression model was also constructed. Additionally, the attributes and variable of the module, module configuration rules and the match of module variables were analyzed. Based on customers' demands, the customized telecommunication product configuration was completed by determining and assigning values to the parameters of each configuration module in GBOM and constraint solving.